Elasticity of Nacrite: Implications for Subduction Zone Dynamics - Ishita Das; Gaurav Shukla (Geochemistry, Geophysics, Geosystems)
Abstract Subduction zones exhibit heterogeneities in composition due to different mineral assemblages transported into the mantle by the descending slabs, thus affecting the seismic properties of the region. These minerals are typically rich in alumina and silica and often contain hydrous phases. Nacrite, Al2Si2O5(OH)4, a mineral consisting of these components, forms in basaltic crust through hydrothermal alteration and is frequently overlooked due to its structural alikeness with its polytypes, making it hard to distinguish by traditional methods. Its occurrence in oceanic sediments and altered basaltic crust significantly impacts the subduction process by facilitating the transport of water into deeper mantle regions. In this study, we investigate the equation of state and elasticity of nacrite using first‐principles calculations based on density functional theory corrected for dispersive forces over its pressure stability range. Anomalous behavior of elastic coefficients are suggestive of a polytypic transformation, evidenced by anomalous softening in the shear modulus and a decrease of approximately 3% in shear wave velocity observed at low pressures (∼ 2 GPa). Our studies indicate that nacrite exhibits a significantly lower shear wave velocity compared to the surrounding mantle, resulting in very high VP/VS ratios. These findings emphasize the role of nacrite in the subduction zones of Japan and Alaska, particularly in the formation of low‐velocity layers. We propose that nacrite's presence is a significant factor explaining these observations, alongside other hydrous minerals like lawsonite, glaucophane, etc., contributing to the low‐velocity layers in these regions.